2016
DOI: 10.3390/cryst6090113
|View full text |Cite
|
Sign up to set email alerts
|

Van Der Waals Heterostructures between Small Organic Molecules and Layered Substrates

Abstract: Two dimensional atomic crystals, like grapheme (G) and molybdenum disulfide (MoS 2 ), exhibit great interest in electronic and optoelectronic applications. The excellent physical properties, such as transparency, semiconductivity, and flexibility, make them compatible with current organic electronics. Here, we review recent progress in the understanding of the interfaces of van der Waals (vdW) heterostructures between small organic molecules (pentacene, copper phthalocyanine (CuPc), perylene-3,4,9,10-tetracarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…So far, relatively few studies exploit the possibility to generate highly predictable selfassembled molecular monolayers on the surface of TMDs 219,252,253,421,422 and impart them on-demand functions. Indeed, the molecular arrangement on TMD surfaces is determined by supramolecular interactions which can be predicted and controlled by molecular design.…”
Section: Discussionmentioning
confidence: 99%
“…So far, relatively few studies exploit the possibility to generate highly predictable selfassembled molecular monolayers on the surface of TMDs 219,252,253,421,422 and impart them on-demand functions. Indeed, the molecular arrangement on TMD surfaces is determined by supramolecular interactions which can be predicted and controlled by molecular design.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Alternatively, graphene has been proposed as an electrode material in organic electronics, 22 with the ability to control molecular assembly to increase the crystallinity and define the orientation of the organic thin film, hence improving its electrical properties. 8 , 23 – 25 …”
Section: Introductionmentioning
confidence: 99%
“…1 A remaining key challenge is finding robust means to controllably select the majority charge carrier type and tune the Fermi level position (i.e., doping) in the 2D semiconductor, as required by the particular device type. 2 Among various chemical and physical methods, [3][4][5][6][7][8][9][10][11][12][13] the deposition of organic molecular layers on 2D materials [14][15][16] is a promising doping approach to avoid structural damage, thereby retaining the desired optical and electrical properties of the 2D materials, as such organic layers are mainly stabilized through non-covalent interactions. 17 Previous studies have revealed that the deposition of suitable molecules can be used to modify the energy levels and the charge density of graphene [18][19][20][21] and semiconducting transition metal dichalcogenides (TMDs) 14,15 through charge transfer (CT).…”
mentioning
confidence: 99%